A high efficiency electric heater based on dual-helical tube and screw-tape for instant water heating. (September 2019) - Liu, Zhiyong; Xu, Kai; Qi, Lingfei; Pan, Hongye; Zhang, Zutao; Pan, Yajia; Yuan, Yanping; Zeng, Yikai
Graphical abstract: Highlights: A high efficiency instantaneous electric water-heater was designed. A dual-helical heating tube was designed to enhance heating efficiency. A screw-tape was utilized to increase the heat-transfer rate. An improved efficiency of 59.6% is achieved in simulation experiments. Abstract: Waste of natural water resources is a serious worldwide challenge, especially in many water shortage countries. There is an urgent and widely known problem that cold-water needs to be released from the faucet before people need warm or hot water. Therefore, there is urgent need for a feasible and effective solution to tackle this problem. In this paper, we proposed a novel instant water-heater based on a dual-helical tube and screw-tape for application in faucets. The proposed water-heater includes four main parts: a control valve module, a cavity structure module, a heating module, and an electronic control module. The heating module is comprised of a dual-helical tube and screw-tape. The dual-helical tube increases the heating area, resulting in uniform heating. The screw-tape possesses a profitable characteristic in that it can make fluid tangential flow and lower the cross-sectional area of the fluid. Based on this advantage, the core region and wall region fluids are mixed, which significantly enhances the heat-transfer rate. The effects of a dual-helical tube and screw-tape with different helical pitch are examined. The experimental results are compared with those obtained using a helical tube/dual-helical tube alone. A 59.6% efficiency improvement is achieved comparing the dual-helical tube and screw-tape with the single helical tube, which suggests the proposed instant electric water-heater is highly efficient and energy saving.